The influence of pH, contact time, ionic strength, temperature, and fullerene on the adsorption of Cu(II) onto magnetic multi-walled carbon nanotubes. Issue 4 (3rd April 2019) - Liu, Peng; Xue, Yun; Ma, Fuqiu
Abstract: The influences of pH, contact time, absorbent dose, temperature and C60 (C(COOH)2 )n on Cu(II) adsorption onto the magnetic multi-walled carbon nanotubes (MMWCNTs) were studied by batch technique. The dynamic process showed that the adsorption of Cu(II) onto MMWCNTs matched well with the pseudo-second-order kinetics model. The adsorption of Cu(II) onto MMWCNTs was dependent on pH values significantly, the adsorption percentage increased observably at pH 5.0–7.0, and then maintained a steady state with pH increased. Through simulating the adsorption isotherms by Langmuir, Freundlich and Dubini-Radushkevich models, respectively, it could be seen that the adsorption pattern of Cu(II) onto MMWCNTs was mainly surface complexation. The presence of C60 (C(COOH)2 )n could enhance the adsorption content of Cu(II) onto MMWCNTs at low pH, but restrained that at higher pH.